Identification of Alnus glutinosa L. and A. incana (L.) Moench. Hybrids in Natural Forests Using Nuclear DNA Microsatellite and Morphometric Markers - Girmantė Jurkšienė (MDPI AG, 2021)
Two alder species (Alnus glutinosa and A. incana) have overlapping distribution, naturally occur in Lithuania, and are considered ecologically and economically important forest tree species. The objective of our study was to estimate the likelihood of spontaneous hybridizations between native alders in natural stands of Lithuania based on leaf morphology and nuclear microsatellite markers. The sampled trees were assigned to the three taxonomic groups of A. glutinosa, A. incana, and potential hybrids based on the leaf and bark morphological traits. The genetic differentiation and potential hybridization between these three groups was tested based on 15 nSSR markers. We identified studied Alnus spp. individuals as pure species and hybrids. Two microsatellite loci were reported as discriminating well between these species. We concluded that our results showed the highest likelihood of two genetic group structures, a clear genetic differentiation between the morphology-based groups of A. glutinosa and A. incana, and rather variable likelihood values in the putative hybrid group. The results provide important implications for genetic conservation and management of Alnus spp.